2012
DOI: 10.1098/rstb.2011.0309
|View full text |Cite
|
Sign up to set email alerts
|

Nitrous oxide production and consumption: regulation of gene expression by gas-sensitive transcription factors

Abstract: Several biochemical mechanisms contribute to the biological generation of nitrous oxide (N 2 O). N 2 O generating enzymes include the respiratory nitric oxide (NO) reductase, an enzyme from the flavo-diiron family, and flavohaemoglobin. On the other hand, there is only one enzyme that is known to use N 2 O as a substrate, which is the respiratory N 2 O reductase typically found in bacteria capable of denitrification… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
91
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(94 citation statements)
references
References 74 publications
(110 reference statements)
2
91
0
1
Order By: Relevance
“…6), while the other factors contributed considerably less to explain the observed N 2 emissions. The dominance of WFPS is in line with common knowledge about the functioning of denitification, given that N 2 production is catalyzed by the enzyme N 2 O-reductase, which in turn is up-regulated by low oxygen concentrations (Spiro, 2012). From calculating fractions it is clear that N 2 is the dominant compound of gaseous losses, often exceeding N 2 O and NO emissions by several magnitudes (Table 3).…”
Section: N 2 Emissions and Total Gaseous Nitrogen Lossessupporting
confidence: 64%
“…6), while the other factors contributed considerably less to explain the observed N 2 emissions. The dominance of WFPS is in line with common knowledge about the functioning of denitification, given that N 2 production is catalyzed by the enzyme N 2 O-reductase, which in turn is up-regulated by low oxygen concentrations (Spiro, 2012). From calculating fractions it is clear that N 2 is the dominant compound of gaseous losses, often exceeding N 2 O and NO emissions by several magnitudes (Table 3).…”
Section: N 2 Emissions and Total Gaseous Nitrogen Lossessupporting
confidence: 64%
“…These results would exclude N 2 O as a regulator of nosZ transcription in B. japonicum. Consistent with this, it has been reported that N 2 O does not appear to regulate the expression of any denitrification gene (5).…”
supporting
confidence: 76%
“…Soybean nodules emit N 2 O under field conditions in the late growth period (1)(2)(3). While N 2 O generation is due to a diversity of microbial enzymes, N 2 O consumption appears to be due exclusively to N 2 O reductase (Nos) (4)(5)(6). Nos catalyzes the two-electron reduction of N 2 O to N 2 .…”
mentioning
confidence: 99%
“…One regulator that mediates this de-repression is the NO-binding protein NsrR. In E. coli, NsrR regulates some 20 genes, including that for flavohaemoglobin (Hmp) which converts NO to N 2 O under anoxic conditions [42].…”
Section: Biological Production and Consumption Of Nitrous Oxidementioning
confidence: 99%
“…(b) Microbiological aspects Of the many factors that contribute to the emission of N 2 O from bacterial populations, one important determinant is the cellular abundance and another is the activities of the enzymes that produce and consume N 2 O [42]. Enzyme abundance is governed by expression of the corresponding genes of regulatory systems and signal transduction pathways that respond to intra-or extracellular signals.…”
Section: Biological Production and Consumption Of Nitrous Oxidementioning
confidence: 99%